The Implementation of 2013 Curriculum in English Teaching: Stories From Rural Areas - Afrianto Daud; Heri Gunawan (Universitas Ahmad Dahlan, 2018)
This study aims to document how the 2103 curriculum has been implemented by English teachers in a high school located in a rural area in Riau province. This research in particular investigates the implementation of Scientific Approach by English teachers in Bunga Raya Siak regency. The study is specifically aimed at investigating two research questions: (1) how the scientific approach has been implemented in the classroom and (2) what problems the teachers face during the implementation. Three English teachers were selected as participants of this study using total sampling technique. Since the study employed mixed method, the data consisted of quantitative and qualitative entities. The quantitative data were obtained from a questionnaire (survey) while the qualitative ones were gained through semi-structured interviews. The results revealed that the teachers have implemented the scientific approach relatively well. This can be seen from the results of the survey in which the overall mean score calculated was categorized ‘very good’. However, the interview data shows that all teachers experienced some problems in implementing this new curriculum. In general, the problems can be classified into four: (a) insufficient English teaching hour; (b) the students’ high diversity in terms of ability; (c) discrepancy between curriculum and national examination contents; and (d) lack of the facility.